Bringing the Harm Home: The Quest for Home Ownership and the Amplification of Social Harm. Issue 3 (4th May 2021) - Schelhase, Marc
ABSTRACT: The article contributes to the debate about the centrality of home ownership in conceptualising and understanding the contemporary political economy through the introduction of a social harm framework. It demonstrates how the focus on social harm offers a more holistic view of the harmful consequences of the privileging of home ownership within the context of political economy. It does so, firstly, by demonstrating the negative medium- and long-term social harms of current housing policies in the UK, namely financial/economic harm, cultural safety and physical, emotional and psychological harms. Secondly, it is possible to draw attention to these harms for individuals or groups that seemingly believe, or are commonly seen to have, benefited from the current structure of home ownership in the UK. And thirdly, it highlights the transformative potential of the social harm approach in terms of developing an alternative to the current variety of residential capitalism in the UK.